The Role of Plasminogen Activator Inhibitor Type 1 (PAI-1) in Placenta-Mediated Pregnancy Complications: A Systematic Review - Agersnap, Ida; Nissen, Peter H.; Hvas, Anne-Mette (Seminars in Thrombosis and Hemostasis, 2022)
Plasminogen activator inhibitor type 1 (PAI-1) is a main inhibitor of fibrinolysis. The PAI-1 gene (SERPINE1) harbors genetic variants with the potential of modifying plasma levels of PAI-1. A delicate balance exists between the coagulation and fibrinolytic system, and changes in PAI-1 have been suggested to compromise establishment of a successful pregnancy. Therefore, this systematic review investigated the association between genetic variants and/or plasma levels of PAI-1 and placenta-mediated pregnancy complications. An extensive literature search was conducted in PubMed, Embase, and Web of Science on the 29th of April 2021. All studies underwent quality rating according to The Study Quality Assessment Tools checklist provided by National Heart, Lung and Blood Institute. A total of 71 studies were included, among which 60 studies investigated PAI-1 genotypes and 11 studies measured PAI-1 plasma levels. In 32 out of 59 studies, no association was found between the PAI-1 4G/5G polymorphism (rs1799768) and placenta-mediated pregnancy complications, which was stated as no significant difference in the genotype distribution comparing women with and without placenta-mediated pregnancy complications or no significantly increased odds of placenta-mediated pregnancy complications carrying the 4G/4G or 4G/5G genotype. Eight out of 11 studies reported significantly higher PAI-1 plasma levels in preeclamptic women than in women without preeclampsia. In conclusion, no clear evidence indicates that PAI-1 polymorphisms are associated with placenta-mediated pregnancy complications, and the possible association between high PAI-1 plasma levels and preeclampsia needs further investigations. Thus, investigation of PAI-1 genotypes and PAI-1 plasma levels does not currently seem to have a place in daily clinical practice managing placenta-mediated pregnancy complications.
Keywords: placenta-mediated pregnancy complications; plasminogen activator inhibitor type 1; low-molecular weight heparin; PAI-1; pregnancy